Development of experimental model of magnetorheological damper for semi-active vibration control - Kasemi, S. M. Hasanul Banna (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Magnetorheological (MR) dampers offer solutions to many engineering disciplines ranging from automotive and civil engineering to biomedical engineering. Many efforts have been taken to model the MR damper and its nonlinear hysteresis phenomena. Although, some important mathematical models have been derived, some problems in implementing the MR damper in real application are yet to be solved. The car industries are growing faster and using modern technology to provide comfort to the passengers. Many control algorithms have been developed and opted to control the vibration of the car. The aim of this research is to use MR damper behaviour to implement a vibration controller. In this research, the methodology adapted to get a control structure is based on experimental results. MR damper is experimentally studied to investigate and establish its behaviour. Force-displacement and forcevelocity responses with varying current have been established to get the MR damper model. The force for upward and downward motions of damper piston is found increasing with current and velocity. In the cycle mode which is the combination of upward and downward motion of the piston, the force having hysteresis behaviour is found to be increasing with current. The energy dissipated is also found to be linear with current. Impedance (force/velocity) analysis has been done in this research. Impedance is found to be very high in low frequency and very small at high frequency. A proportional-integral-derivative (PID) controller based on the established characteristics for a quarter car suspension model has been adapted in this study. A fuzzy rule based PID controller is opted to achieve better response for a varying frequency input. The outcome of this study can be used in the modelling of MR damper and applied to control engineering. Moreover, the identified behaviour can help in further development of MR damper technology. This behaviour is more practical as it is obtained from experiments.